Cardiovascular disease risk associated with serum apolipoprotein B is modified by serum vitamin A. (October 2017) - Olsen, Thomas; Vinknes, Kathrine J.; Svingen, Gard F.T.; Pedersen, Eva R.; Tell, Grethe S.; Blomhoff, Rune; Drevon, Christian A.; Ueland, Per M.; Midttun, Øivind; Refsum, Helga; Nygård, Ottar K.
Abstract: Background and aims: Apolipoproteins B (apoB) and A1 (apoA1) are major protein constituents of low-density and high-density lipoproteins, respectively, and serum concentrations of these apolipoproteins are associated with risk of atherosclerosis. Vitamin A (VA) has been implicated in lipoprotein metabolism. We evaluated the associations of serum apoB, apoA1 and their ratio (apoBAR) with risk of incident acute myocardial infarction (AMI) and the possible modification by serum VA. Methods: Risk associations were assessed by Cox regression, and presented as hazard ratios (HRs) per standard deviation (SD) increment in log-transformed values of the lipid parameters, among 4117 patients with suspected stable angina pectoris, located in Western Norway. Interactions with VA were evaluated by including interaction terms in the models. The multivariate model included age, sex, smoking, hypertension, number of stenotic coronary arteries, left ventricular ejection fraction, C-reactive protein, estimated glomerular filtration rate and statin treatment at discharge. Results: Median (25th, 75th percentile) age of the 4117 patients (72% male) was 62 (55, 70) years. ApoB and apoA1 were higher among patients in the upper versus lower tertiles of VA. During a median of 4.6 (3.6, 5.7) years of follow-up, 8.2% of patients experienced an AMI. Overall, we observed no significant associations between lipid parameters and AMI after multivariate adjustment. However, apoB and apoBAR were associated with AMI among patients in the upper tertile of VA (HR per SD 1.35, (95% CI: 1.11–1.65), and 1.42 (1.16–1.74), respectively, p for interactions ≤0.003). Conclusions: The associations of apoB and apoBAR with incident AMI were confined to patients with elevated VA. Highlights: In general, apolipoprotein B was not associated with acute myocardial infarctions (AMI). The association of apolipoprotein B with AMI was modified by vitamin A. The association of apolipoprotein B to A1 ratio with AMI was modified by vitamin A.